Effect of Return on Assets, Debt to Equity Ratio, Firm Size and Current Ratio on Dividend Payout Ratio (Case Study on Food and Beverage Sub-sector Manufacturing Companies Listed on the IDX for the 2016-2020 Period) - Simbolon, Jesica Natalia Br; Sitanggang, Tina Novianti; Simorangkir, Desliani Natalia; Naibaho, Junianti Ramayana; Halawa, Luther Berkat Jaya (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The purpose of this research observation is to find out whether the proposed hypothesis is the results obtained, namely whether partially and simultaneously on the Return On Assets, Debt To Equity Ratio, Firm Size and Current Ratio variables to the Dividend Payout Ratio. This research is a causal associative research. A total population of 8 companies were selected by purposive sampling. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that Return on Assets does not significantly affect the Dividend Payout Ratio, Debt to Equity Ratio and Firm Size has a negative and insignificant effect on the Dividend Payout Ratio, Current Ratio has a positive and significant effect on the Dividend Payout Ratio. So the overall results of Return on Assets, Debt to Equity Ratio, Firm Size, and Current Ratio have a partial and significant effect on the Dividend Payout Ratio in manufacturing companies in the food and beverage sub-sector listed on the IDX for the period 2016 – 2020. By obtaining a total value of Adjusted R Square as many as 0.146, these four variables can explain or give an effect of 14.6% and 85.4% given other variables.